Wide-range precision RF peak detectors. (September 2018) - Ciubotaru, Alexandru A.
Abstract: A significant increase in the accuracy of a conventional bipolar monolithic radio-frequency bipolar peak detector is robustly achieved over a wide amplitude range using a simple nonlinear loading circuit. The loading circuit provides two voltage-controlled auxiliary currents which cancel the errors by altering the original DC currents flowing through the core transistors, according to the level of the detected voltage. Expressions are derived for the auxiliary currents for perfect error cancellation; a good approximation is provided by a simple cross-coupled transistor pair, but more complex circuit structures can be employed for enhanced range and/or robustness. Because the loading circuit operates essentially at DC, the high-frequency nature of the original peak detector is preserved. The presented concept and its various circuit implementations are discussed and validated in simulation, and are expected to work in a large variety of modern bipolar or BiCMOS integrated-circuit technologies, where parasitics-free, simple exponential-law models accurately represent the operation of the transistors up to very high frequencies.